Cotton Cost-Return Budget in South Central and Southeast Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2003)
This publication projects a budget that reflects expected income and costs based on production of cotton in south central and southeast Kansas.
MF939_2003_10
Keywords: MF939; Economics; Crops; MF